Interaction of adriamycin with DNA as studied by resonance Raman spectroscopy. - Manfait, M (1982)
Raman and resonance Raman spectra of the complex DNA-adriamycin in aqueous solution have been recorded and analysed. Calf thymus DNA was used and it is found that in the complex DNA-adriamycin the chromophore of adriamycin is intercalated in the GC sequences. The substituents on the rings give hydrogen bonding interactions with the base pairs above and below the intercalation site. It is suggested from the Raman and resonance Raman spectral modifications that the phenolic groups of the chromophore are involved in the drug-DNA intercalation, in addition to pi-pi, hydroxyl and amino group interactions.